The protective effect of peroxiredoxin II on oxidative stress induced apoptosis in pancreatic β-cells - Zhao Fang; Wang Qinghua (Cell & Bioscience, 2012)
Abstract Excessive loss of pancreatic β-cells, mainly through apoptosis, contributes to the development of diabetic hyperglycemia. Oxidative stress plays a major role in the process of β-cell apoptosis due to low expression level of endogenous antioxidants in the β-cells. Peroxiredoxins (PRDX) are a family of peroxide reductases which uses thioredoxin to clear peroxides. Several members of PRDX have been found in β-cells and recent studies suggested that these antioxidant enzymes possess protective effects in β-cells against oxidative stress mediated apoptosis. In this study, we aimed to investigate the role of PRDX2 in modulating β-cell functions. We detected the expression of PRDX2 both at the transcript and protein levels in the clonal β-cells INS-1 and MIN6 as well as rodent islets. Western blot showed that treatment of MIN6 β-cell line with proinflammatory cytokines, palmitic acid or streptozotocin dose- or time-dependently increased apoptosis, which was associated with reduced endogenous expression levels of PRDX2. To examine the role for PRDX2 in the apoptotic stimuli-induced β-cell apoptosis, we used plasmid overexpression and siRNA knockdown strategies to investigate whether the elevation or knockdown of PRDX2 affects stimuli-induced apoptosis in the β-cells. Remarkably, overexpression of PRDX2 in MIN6 cells significantly attenuated the oxidative stresses mediated apoptosis, as evaluated by cleaved caspase 3 expression, nuclear condensation and fragmentation, as well as FACS analysis. Conversely, attenuation of PRDX2 protein expression using siRNA knockdown exaggerated the cell death induced by proinflammatory cytokines and palmitic acid in the MIN6 cells. These results suggest that PRDX2 may play a protective role in pancreatic β-cells under oxidative stress.